1973
DOI: 10.2307/525857
|View full text |Cite
|
Sign up to set email alerts
|

The Forum and Basilica of Roman Leicester

Abstract: Excavations on the western half of Insula XXII revealed remains of a forum and basilica of late Hadrianic date. They succeeded a first-century occupation of possibly military character. The forum was renovated during the third century, and the southwest corner extensively repaired at the beginning of the fourth century. The whole structure was apparently destroyed by fire not earlier than the third quarter of the fourth century, but quite possibly much later. * The writers are greatly indebted to the Editor, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…61 To the north-east, along the Fosse Way at Leicester, there seems to have been continuous occupation from the Conquest onwards (with limited indications of a Roman military phase) of the late Iron Age oppidum with evidence of buildings both of timber and of masonry on different alignments to and pre-dating the laying out of streets, which, in the St Nicholas area, were metalled by A.D. 120. 62 The forum basilica followed later, c. A.D. 130-40/50, 63 and the Jewry Wall public baths a little later still, c. A.D. 145-50. 64 If we go by the date of the laying out of the streets, the civitas of the Corieltauvi was not created until the early second century, again some 30 years or more after the likely withdrawal date of the putative garrison.…”
Section: Civitates the Forum Basilica And Public Building In The Townsmentioning
confidence: 99%
“…61 To the north-east, along the Fosse Way at Leicester, there seems to have been continuous occupation from the Conquest onwards (with limited indications of a Roman military phase) of the late Iron Age oppidum with evidence of buildings both of timber and of masonry on different alignments to and pre-dating the laying out of streets, which, in the St Nicholas area, were metalled by A.D. 120. 62 The forum basilica followed later, c. A.D. 130-40/50, 63 and the Jewry Wall public baths a little later still, c. A.D. 145-50. 64 If we go by the date of the laying out of the streets, the civitas of the Corieltauvi was not created until the early second century, again some 30 years or more after the likely withdrawal date of the putative garrison.…”
Section: Civitates the Forum Basilica And Public Building In The Townsmentioning
confidence: 99%
“…Roman Leicester, by contrast, did not see the construction of a street grid until the early second century when it is usually suggested that the town's civic status was formally established, but during the course of the second century it was provided with some of the public architecture of forum, basilica and public baths needed for the proper establishment of civic life and authority. The circumstances of their excavation mean that the extent to which these foci subsequently thrived as authoritative and economic resources for the wider community is poorly understood, but the level of continual refurbishment of rooms in the forum and its neighbouring roads noted by Hebditch and Mellor () would suggest they did. Unlike Leicester, none of the roadside settlements have evidence for investment in substantial public architecture though the presence of bath houses and temples at several sites acts as a useful guide to the emerging roles of each as they provide some indication of local euergetism.…”
Section: Urbanism In Two Contrasting Landscapesmentioning
confidence: 99%
“…Balty uses identification of benches, architectural form, position, and internal decoration as criteria. 34 At Silchester (figure 7.1), the earliest commentators argued that the central room in the western range of the basilica was the curia, but it seems more likely that this was a shrine. The only probable example of the freestanding temple form is at Verulamium where three abutting buildings lie at the southern end of the forum, opposite the basilica (figure 7.2).…”
Section: The Forum-basilica In Roman Britain 137mentioning
confidence: 99%